ANALISIS PENDAPATAN PETANI AGRORESTRI KEMIRI DAN KAKAO DI DESA SIGIMPU KECAMATAN PALOLO KABUPATEN SIGI - Cici, .; Umar, Syukur; Pribadi, Hendra (Jurnal Warta Rimba, 2018)
Forest is an ecosystem characterized by a closure of more or less densely packed trees, consisting of multiple stylized characteristics such as species composition, structure, age classes, and generally encompassing grasslands, small rivers and wildlife. Agro-forestry is a blend of agricultural crops and forestry. With the existence of agro-forestry is expected to maintain the function of forest in the form of agricultural processes but it also can increase people's income. Community-based in many terms used by many who have been able to encourage community access to forest resources management.Â  The purpose of this study is to determine the value of income on agro-forestry yields of candlenuts and cocoa. the research period is conducted for three months, ie November 2016 until January 2017, located in the village of Sigimpu Palolo district of Sigi Regency. The data were collected through questionnaire. Data analysis used was multiple linear regression analysis. The research results reveal that agro-forestry farmers can produce 2.496.96 kg candle nuts per year, while for cacao farmers can produce 276.58 kg per year. The analysis results indicate that the average income of agro-forestry farmers of candle nuts and cacao in the village is Rp. 28.397.916.73/year.Keywords: Income Analysis of Agroforestry Farmers of Candle Nut and Cacao In Sigimpu Village